1993
DOI: 10.1002/pssa.2211350103
|View full text |Cite
|
Sign up to set email alerts
|

Structure Model of Aurivillius Compounds. An EXAFS Study

Abstract: Aurivillius phases are compounds with the general formula (Am−1BmO3m+1)2− (Bi2O2)2+ that consist of (m − 1) perovskite‐like units interrupted by bismuth oxide layers. Compounds with A = {Ba2+; Sr2+}, B = {Nb5+}, and m = 2 are studied by EXAFS spectroscopy and X‐ray diffraction. The lattice parameters a and c of the tetragonal phase, studied by X‐ray diffraction, increase with increasing Ba content. The short‐range order environment of Ba, Sr, and Bi ions are analyzed for several Ba:Sr ratios using EXAFS spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…SrBi 2 Nb 2 O 9 is a member of the family of the bismuth layer-structured materials, [1][2][3][4][5][6] which are interesting ferroelectrics for technical devices. The crystal structure is composed of ͑Bi 2 O 2 ͒ 2+ layers interleaved with perovskite-type blocks ͑A m−1 B m O 3m+1 ͒ 2− .…”
mentioning
confidence: 99%
“…SrBi 2 Nb 2 O 9 is a member of the family of the bismuth layer-structured materials, [1][2][3][4][5][6] which are interesting ferroelectrics for technical devices. The crystal structure is composed of ͑Bi 2 O 2 ͒ 2+ layers interleaved with perovskite-type blocks ͑A m−1 B m O 3m+1 ͒ 2− .…”
mentioning
confidence: 99%
“…The dielectric properties were measured by an HP 4284A LCR meter. 5 Moreover, it can be found that the configuration of the first and second coordination shell peaks for Bi L 3 edge of the central Bi atom in Ba 0.6 Sr 0.4 Bi 2 Nb 2 O 9 is very similar to that of Nd L 3 edge of the central Nd atom in SrBi 1.6 Nd 0.4 Nb 2 O 9 . XAFS measurements at Nd L 3 edge were performed using synchrotron radiation at the National Synchrotron Radiation Laboratory.…”
mentioning
confidence: 86%
“…The Aurivillius family has attracted considerable attention due to their large remanent polarization, lead-free nature, relatively low processing temperatures and other characteristics [7][8][9][10][11][12][13][14][15][16][17]. Its general formula is [Bi 2 O 2 ] 2+ [A n−1 B n O 3n+1 ] 2− , where A can be Sr 2+ , Ca 2+ , etc.…”
Section: Introductionmentioning
confidence: 99%
“…The origin of the relaxor behavior for these materials have been associated to a positional disorder of cations on A or B sites of the perovskite blocks that delay the evolution of long-rage polar ordering [7]. SrBi 2 Nb 2 O 9 is a member of this family [11][12][13][14][15][16], consisting of octahedra in the perovskite blocks sandwiched by two neighboring (Bi 2 O 2 ) 2+ layers along the c-axis in a unit cell. Its ferroelectric properties can be affected by the crystallographic orientation due to their anisotropic crystal structure.…”
Section: Introductionmentioning
confidence: 99%